Uncovering the mask of the Simulium feuerborni complex (Diptera: Simuliidae): Description of a new pseudocryptic species Simulium pairoti from Malaysia - Ya'cob, Zubaidah; Takaoka, Hiroyuki; Low, Van Lun; Sofian-Azirun, Mohd (Elsevier, 2017)
A black fly species of the Simulium feuerborni species-group of Simulium (Nevermannia) from Cameron Highland, Peninsular Malaysia, previously regarded as S. feuerborni Edwards, originally described from East Java, is described as Simulium pairoti sp. nov. based on complete life stages. High intraspecific variations in the arrangement of the six pupal gill filaments, length of the stalk of the ventral paired filaments, and length of the anterodorsal projection of the cocoon, are noted in this species. This new species is readily distinguished from its congeners by having the characters of male genitalia with simple lamellate ventral plate, short inwardly-twisted styles, several parameral hooks, and a simple narrow median sclerite. Morphological data reported herein plus the chromosomal and molecular data presented elsewhere support S. pairoti as a novel pseudocryptic species.